If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x * 5x + 4x + 2) + -1(5x * 5) = 7x + 10 Reorder the terms for easier multiplication: (5 * 5x * x + 4x + 2) + -1(5x * 5) = 7x + 10 Multiply 5 * 5 (25x * x + 4x + 2) + -1(5x * 5) = 7x + 10 Multiply x * x (25x2 + 4x + 2) + -1(5x * 5) = 7x + 10 Reorder the terms: (2 + 4x + 25x2) + -1(5x * 5) = 7x + 10 Remove parenthesis around (2 + 4x + 25x2) 2 + 4x + 25x2 + -1(5x * 5) = 7x + 10 Reorder the terms for easier multiplication: 2 + 4x + 25x2 + -1(5 * 5x) = 7x + 10 Multiply 5 * 5 2 + 4x + 25x2 + -1(25x) = 7x + 10 Remove parenthesis around (25x) 2 + 4x + 25x2 + -1 * 25x = 7x + 10 Multiply -1 * 25 2 + 4x + 25x2 + -25x = 7x + 10 Reorder the terms: 2 + 4x + -25x + 25x2 = 7x + 10 Combine like terms: 4x + -25x = -21x 2 + -21x + 25x2 = 7x + 10 Reorder the terms: 2 + -21x + 25x2 = 10 + 7x Solving 2 + -21x + 25x2 = 10 + 7x Solving for variable 'x'. Reorder the terms: 2 + -10 + -21x + -7x + 25x2 = 10 + 7x + -10 + -7x Combine like terms: 2 + -10 = -8 -8 + -21x + -7x + 25x2 = 10 + 7x + -10 + -7x Combine like terms: -21x + -7x = -28x -8 + -28x + 25x2 = 10 + 7x + -10 + -7x Reorder the terms: -8 + -28x + 25x2 = 10 + -10 + 7x + -7x Combine like terms: 10 + -10 = 0 -8 + -28x + 25x2 = 0 + 7x + -7x -8 + -28x + 25x2 = 7x + -7x Combine like terms: 7x + -7x = 0 -8 + -28x + 25x2 = 0 Begin completing the square. Divide all terms by 25 the coefficient of the squared term: Divide each side by '25'. -0.32 + -1.12x + x2 = 0 Move the constant term to the right: Add '0.32' to each side of the equation. -0.32 + -1.12x + 0.32 + x2 = 0 + 0.32 Reorder the terms: -0.32 + 0.32 + -1.12x + x2 = 0 + 0.32 Combine like terms: -0.32 + 0.32 = 0.00 0.00 + -1.12x + x2 = 0 + 0.32 -1.12x + x2 = 0 + 0.32 Combine like terms: 0 + 0.32 = 0.32 -1.12x + x2 = 0.32 The x term is -1.12x. Take half its coefficient (-0.56). Square it (0.3136) and add it to both sides. Add '0.3136' to each side of the equation. -1.12x + 0.3136 + x2 = 0.32 + 0.3136 Reorder the terms: 0.3136 + -1.12x + x2 = 0.32 + 0.3136 Combine like terms: 0.32 + 0.3136 = 0.6336 0.3136 + -1.12x + x2 = 0.6336 Factor a perfect square on the left side: (x + -0.56)(x + -0.56) = 0.6336 Calculate the square root of the right side: 0.79598995 Break this problem into two subproblems by setting (x + -0.56) equal to 0.79598995 and -0.79598995.Subproblem 1
x + -0.56 = 0.79598995 Simplifying x + -0.56 = 0.79598995 Reorder the terms: -0.56 + x = 0.79598995 Solving -0.56 + x = 0.79598995 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.56' to each side of the equation. -0.56 + 0.56 + x = 0.79598995 + 0.56 Combine like terms: -0.56 + 0.56 = 0.00 0.00 + x = 0.79598995 + 0.56 x = 0.79598995 + 0.56 Combine like terms: 0.79598995 + 0.56 = 1.35598995 x = 1.35598995 Simplifying x = 1.35598995Subproblem 2
x + -0.56 = -0.79598995 Simplifying x + -0.56 = -0.79598995 Reorder the terms: -0.56 + x = -0.79598995 Solving -0.56 + x = -0.79598995 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.56' to each side of the equation. -0.56 + 0.56 + x = -0.79598995 + 0.56 Combine like terms: -0.56 + 0.56 = 0.00 0.00 + x = -0.79598995 + 0.56 x = -0.79598995 + 0.56 Combine like terms: -0.79598995 + 0.56 = -0.23598995 x = -0.23598995 Simplifying x = -0.23598995Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.35598995, -0.23598995}
| y^2+12y+x+20=0 | | 7/5+1/2t=2 | | 6x-15-15=360 | | -42=-18-16c | | 2(-3x+2)-2x=68 | | 3x+2x+10=10 | | 4+(11/x)+(2/5)=7/2x | | 3y=6x-7 | | 5y+6=11 | | 64x+40=11-x+3 | | 4+11/x+2/5=7/2x | | 2b-6+2+7=10 | | x/7-2x=2 | | 43(19x-7x)+32(19-7x)=25(7x-19) | | 1-5/7 | | 4x+(1/6)=1/12 | | 4x+(1/6)=1-12 | | 1x+7=-9 | | 1/5(2x-1)=4 | | 6x^2-3xy-11x+4y=-10 | | 2x-1+75=105 | | 28c+539=207-138x | | -8+2(x+7)=22 | | x/3-4/15=-14/15 | | y+(7.5)=-12.2 | | 2.8x+53.9=20.7-14.8x | | 1+57=x | | 2ex-1=0 | | 1+57=0 | | 9/5+2/5x=67/30+7/6x+1/6 | | 4(x+1.2)=3x+6.9 | | 3x+5=ax+b |